Integrating Facial Recognition and GPS Technology for Efficient Attendance Management in Educational Institutions - M Rhifky Wayahdi; Fatahul Ahmad Dzikri (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This study explores the integration of facial recognition and GPS technology to enhance attendance management systems in educational institutions. By employing a two-layer verification process that combines face validation and location validation, the proposed system addresses common challenges of traditional attendance methods, such as proxy attendance and inefficient data management. The system not only improves accuracy and security but also provides valuable insights into attendance patterns through location-based analytics. Despite its advantages, the research highlights the need to address challenges related to data privacy, security, and user acceptance for successful implementation. Overall, this study contributes to the development of modern attendance management solutions, demonstrating the potential for increased efficiency and effectiveness in educational environments.